Profile of Student Achievement Through PBL-Based Sound Wave Worksheets - Azrul Hamidi; Danang Habib Pratama; Jumadi; Sabar Nurohman (Methods in Science and Technology Studies, 2025)
The purpose of this project is to create sound wave worksheets based on PBL that will enhance class VIII students' learning results. The development of the LKPD that was carried out obtained the result that the PBL-based sound wave LKPD was feasible to use to improve student learning outcomes. This study has a one-group posttest-only design and is a quasi-experimental investigation. The field test was carried out at SMP Negeri 24 Padang class VIII obtained the result that LKPD could improve student learning outcomes. Data analysis using SPSS 25 One Grub Posttest-Only Design with Sig. (2-tailed) 0.006. This learning outcome profile can provide an overview of students' understanding of the concept of noise pollution and their ability to identify, analyze, and find solutions to noise pollution problems after going through PBL learning using worksheets.